2021
DOI: 10.1111/famp.12645
|View full text |Cite
|
Sign up to set email alerts
|

Religious Coping and Gender Moderate Trajectories of Marital Love among Black Couples

Abstract: An increasing body of work documents the roles of religion and spirituality in Black American marriages. We built on this research to examine religious coping as a potential cultural resource for Black marriages using a dyadic analytic approach with longitudinal data. Specifically, we investigated the effects of positive (i.e., sense of spiritual connectedness) and negative (i.e., spiritual tension or struggle) religious coping on trajectories of marital love reported by wives and husbands in 161 Black, marrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Previous research suggests that religiosity is essential for Black couples (e.g., Jenkins et al, 2022). Because this factor is essential in Black couples, adding religion and spirituality as a buffer or control in future research is recommended.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Previous research suggests that religiosity is essential for Black couples (e.g., Jenkins et al, 2022). Because this factor is essential in Black couples, adding religion and spirituality as a buffer or control in future research is recommended.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Positive religious coping is typically associated with higher marital adjustment (e.g., Fallahchai et al, 2021), whereas the association between negative religious coping and marital processes is mixed. On the one hand, research has shown that negative religious coping may improve wives' ratings of marital love in the long run among African American couples, as wives' ability to freely express their displeasure with their faith to their spouse reflects higher levels of safety in their relationships (Jenkins et al, 2022). On the other hand, there is also research suggesting that among married Iranian Muslim couples, negative religious coping was associated with lower marital adjustment (Fallahchai et al, 2021).…”
mentioning
confidence: 99%